Analisis Yuridis Terhadap Penyelesaian Sengketa Wanprestasi Dalam Perjanjian Dana Beasiswa Pendidikan (Studi Putusan Nomor 178/Pdt.G/2019/Pn.Tjk) - Zainab Ompu Jainah; S. Endang Prasetyawati; Putri Mawardita Puspitasari (Widya Yuridika, 2021)
Default is the implementation of obligations that are not fulfilled or broken promises or negligence made by the debtor either due to not carrying out what has been promised or even doing something that according to the agreement cannot be done. The problem in this study is how to resolve default disputes in the educational scholarship fund agreement based on decision Number 178 / Pdt.G / 2019 / PN.Tjk and how the judges' legal considerations against default disputes in the educational scholarship fund agreement based on decision Number 178 / Pdt.G / 2019 / PN.Tjk. The research method used is a normative juridical approach and an empirical approach. Data collection procedure consists of the study of literature (Library Research)and field (Field Research). Meanwhile, data processing is done by using the methods of editing, systematizing and classifying the data. The analysis used is qualitative. Based on the results of the study, it can be concluded that the settlement of default disputes in the educational scholarship fund agreement is the compensation for damages accompanied by the cancellation of the agreement. Then the judge's legal consideration of the dispute of default in the educational scholarship fund agreement is that the defendant has not at all carried out his achievements or obligations to the plaintiff since graduating from the Specialist Doctor Education Program (PPDS) Obstetrics and Gynecology Study Program at the Faculty of Medicine, Diponegoro University. The suggestion in this study is that dispute resolution using a non-litigation approach is the best way and judges in deciding a case must still refer to the agreement made by the parties.